CCAFS involvement in the Global Commission on Adaptation puts 300 million small-scale farmers on the pathway towards enhanced resilience - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CCAFS informed the food security work of the Global Commission on Adaptation by co-authoring the food security chapter in the GCA Report as well as Bruce Campbell, CCAFS Director, co-leading the Food Security Action Track. In 2019, this Action Track received USD 790 million financial commitments, of which USD 650 million will go to the CGIAR. Initiatives under this Action Track have been shaped by CCAFS, including developing a blueprint to scale-up sustainable and equitable climate advisory services.